Beban Masyarakat Adat Menghadapi Hukum Negara - Syamsudin Syamsudin (Jurnal Hukum IUS QUIA IUSTUM, 2008)
The most common type of conflict involving indigenous people is the dispute  on the ownership of economic resources and cultural sites which are convicted  and is guaranteed as traditional indigenous rights. In this regard, indigenous people stand vis a vis with investors’ interest  which is usually safeguarded by state legal instruments. Indigenous people are shaky  in this kind of conflict, and in the factual cases, the process to weaken and destroy indigenous community has  been made through regulations, policies  as well as the real actions made by the government.